Pembangunan Perisian Kursus Multimedia Berasaskan Web Untuk Kursus TD5004 : Analisis dan Rekabentuk Sistem - Zuriani, Ahmad Zulkarnain (2001)

(untitled)
This research describes a project to develop a web-based interactive multimedia courseware for TD 5004: System Analysis and Design. The course is pre-requisite which compulsory to non IT for program Master of Science (Information Technology) (MSc IT) student in Universiti Utara Malaysia. A Prototype was developed using Incremental Prototyping Methodology. An evaluation has been conducted to evaluate the prototype. From the result, analysis has been done to support the feedback given by respondent. Some further recommendations were addressed to produce more effective courseware.